OSTEOPOROSIS IN AUTOIMMUNE DISEASES - Tomašević-Todorović, Snežana; Ilić, Nataša; Savić, Damjan; Jelčić, Sandra (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Osteoporosis is one of the most common extra-articular complications in many chronic inflammatory rheumatic diseases, including rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, and systemic lupus erythematosus. Methods: We searched the PubMed, Scopus, and Web of Science databases for studies published within the last 10 years. This is a review article.Results: Most studies on postmenopausal women have found a correlation between high levels of pro-inflammatory markers and increased bone loss. Literature data indicate a link between a low risk of major osteoporotic fractures, hip fractures, and non-vertebral fractures in patients with PsA who are on disease-modifying therapies. Patient assessment in autoimmune rheumatic inflammatory diseases includes medical history, clinical examination, fracture risk assessment, laboratory tests, and bone densitometry. The lack of adequate diagnosis and treatment of osteoporosis is influenced by factors such as insufficient knowledge about osteoporosis and its therapeutic benefits, concerns about potential side effects of treatment, low motivation, and inadequate patient education on the subject. Several methods have been developed to reduce prescribing errors and oversights, with the Fracture Liaison Service proving to be the most effective. Strategies for managing osteoporosis include patient education, lifestyle modifications, fall prevention, proper nutrition, disease activity control, and the introduction of osteoporosis medication.Conclusion: Despite significant advances in prevention, diagnosis, and treatment, the prevalence of osteoporosis remains high and requires timely recognition and a more comprehensive approach. Assessing risk factors for falls and fractures, as well as recovery potential, is crucial in patients with autoimmune rheumatic inflammatory diseases.
Keywords: osteoporosis; prevalence; risk factors; fractures; therapy